Engineering an automated microbubble-assisted hybrid photobioreactor for CO2 capture and valorisation to polyhydroxybutyrate in indigenous algal biomass - Dey, Saptarshi; Sahu, Abhishek; Dalvi, Vivek; De, Biswajit Samir; Malik, Anushree (Frontiers in Chemical Engineering, 2025)
The integration of microalgal systems into carbon capture technologies offers a dual advantage; the mitigation of anthropogenic CO2 emissions and the sustainable production of high-value macromolecules. This study presents the engineering and pilot-scale operation of a 200 L microbubble-assisted hybrid photobioreactor for CO2 bio-fixation. Subsequent valorisation into lipids and biopolymers was obtained using an indigenous alga, Poterioochromonas malhamensis. A novel 3D-printed microbubble generator assembly (MBG) was retrofitted to a 1.2 m carbonation column (CC) and integrated with a 200 L high-rate algal pond (HRAP). Sequential high-speed bubble imaging at different column heights (H) under different liquid flow (QL) and gas flow (QG) regimes was processed and interpreted using a MATLAB based bubble analyser. A Gaussian distribution function was used to establish the most probable bubble diameter in the range 400–800 µm while achieving microbubble density of 61%–90% in the carbonation column to support efficient gas–liquid exchange. The hybrid reactor was further automated using a real-time pH feedback loop for CO2 dosing under photoautotrophic conditions with 5% (v/v) CO2 supplementation. The system maintained the culture media bicarbonate buffer in the optimal range (pH 7.2–8.5). The hybrid reactor yielded 0.423 gL−1 of biomass with a carbon content of 43.06% DCW, a CO2 bio-fixation rate of 44.05 mgL−1d−1, and polyhydroxybutyrate (PHB) content of 5.79% DCW. Our findings demonstrate the scalability, automation potential, and bioproduct yield enhancements of the hybrid system, making it a viable model for CCUS (carbon capture, utilization, and storage) through algal valorisation. The approach offers a technically sound, energy-efficient route for transforming inorganic carbon into commercially relevant algal macromolecules.